S-thanatin functionalized liposome potentially targeting on Klebsiella pneumoniae and its application in sepsis mouse model - Fan, Xiaobo; Fan, Juxiang; Wang, Xiyong; Wu, Pengpeng; Wu, Guoqiu (Frontiers in Pharmacology, 2015)
S-thanatin (Ts) was a short antimicrobial peptide with selective antibacterial activity. In this study, we aimed to design a drug carrier with specific bacterial targeting potential. The positively charged Ts was modified onto the liposome surface by linking Ts to the constituent lipids via a PEG linker. The benefits of this design were evaluated by preparing a series of liposomes and comparing their biological effects in vitro and in vivo. The particle size and Zeta potential of the constructed liposomes were measured with a Zetasizer Nano ZS system and a confocal laser scanning microscope. The in vitro drug delivery potential was evaluated by measuring the cellular uptake of encapsulated levofloxacin using HPLC. Ts-linked liposome or its conjugates with quantum dots favored bacterial cells, and increased the bacterial uptake of levofloxacin. In antimicrobial assays, the Ts and levofloxacin combination showed a synergistic effect, and Ts-LPs-LEV exhibited excellent activity against the quality control stain Klebsiella pneumoniae ATCC 700603 and restored the susceptibility of multidrug-resistant K. pneumoniae clinical isolates to levofloxacin in vitro. Furthermore, Ts-LPs-LEV markedly reduced the lethality rate of the septic shock and resulted in rapid bacterial clearance in mouse models receiving clinical multidrug resistant (MDR) isolates. These results suggest that the Ts-functionalized liposome may be a promising antibiotic delivery system for clinical infectious disorders caused by MDR bacteria, in particular the sepsis related diseases.